2020
DOI: 10.1016/j.eclinm.2020.100609
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of COVID-19 by analysis of breath with gas chromatography-ion mobility spectrometry - a feasibility study

Abstract: Background There is an urgent need to rapidly distinguish COVID-19 from other respiratory conditions, including influenza, at first-presentation. Point-of-care tests not requiring laboratory- support will speed diagnosis and protect health-care staff. We studied the feasibility of using breath-analysis to distinguish these conditions with near-patient gas chromatography-ion mobility spectrometry (GC-IMS). Methods Independent observational prevalence studies at Edinburgh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
220
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(230 citation statements)
references
References 29 publications
9
220
1
Order By: Relevance
“…This was however not within the scope of the current study. The laboratory identification of the specific VOC pattern is still in its infancy, but some current studies under review and also a peer-reviewed one showed SARS-CoV-2 specific biomarkers in breath samples detectable by gas chromatography-ion mobility spectrometry 27,28 , which also support our hypothesis. Scent dogs should be considered an addition to the gold standard RT-PCR, for rapid testing in situations where great numbers of people from different origins come together.…”
Section: Discussionsupporting
confidence: 81%
“…This was however not within the scope of the current study. The laboratory identification of the specific VOC pattern is still in its infancy, but some current studies under review and also a peer-reviewed one showed SARS-CoV-2 specific biomarkers in breath samples detectable by gas chromatography-ion mobility spectrometry 27,28 , which also support our hypothesis. Scent dogs should be considered an addition to the gold standard RT-PCR, for rapid testing in situations where great numbers of people from different origins come together.…”
Section: Discussionsupporting
confidence: 81%
“…can also be used to monitor naturally 323 occurring methanol during liquor distillation (e.g., fruit spirit or whisky), detect methanol in the breath of methanol poisoning victims to initiate immediate and appropriate treatment with better chance of recovery, 324 and detect the presence of methanol in sanitizers, responsible for 4700 deaths in Iran 325 and USA 326 during the recent COVID-19 pandemic. Even screening for COVID-19 by a quick breath test might be possible after recent research 327 suggested methanol as one of the tentative breath markers of the disease. Or, a sensor enabled by a catalytic filter can selectively detect acetone in the breath.…”
Section: Materials Horizons Reviewmentioning
confidence: 99%
“…During 2020, the human race suffered from the COVID-19 pandemic (1-6) but fortunately learned the importance of controlling transmission through air (7)(8)(9)(10)(11). As a main source of aerosol spread of respiratory viruses, exhaled breath of patients has been confirmed as a potential risk using various methods of sampling and subsequent testing (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Several groups have reported SARS-CoV-2 positivity in samples of exhaled breath condensate (EBC) (21)(22)(23)(24)(25), and based on Ct values, Ma et al further showed that EBC-positive COVID-19 patients exhaled millions of SARS-CoV-2 RNA copies per hour (23).…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have reported SARS-CoV-2 positivity in samples of exhaled breath condensate (EBC) (21)(22)(23)(24)(25), and based on Ct values, Ma et al further showed that EBC-positive COVID-19 patients exhaled millions of SARS-CoV-2 RNA copies per hour (23). Standard diagnosis of viruses based on swabs or serum has been rapidly developed (17,(26)(27)(28)(29), while auxiliary methods, such as trace biomarkers of COVID-19 in exhalations, have also been explored (18)(19)(20). Nevertheless, there is an urgent need for novel methods to detect SARS-CoV-2 in the transmission path.…”
Section: Introductionmentioning
confidence: 99%